Wartawan Profesional dan Gratifikasi: Antara Hukum dan Realitas Sosial - Fadia Anggraini Prayudistian; Sofia Nur Isma; Moch Syahri; Moh Fikri Zulfikar (Fidikom UIN Jakarta, 2023)
This article aims to (1) provide detention and explanation related to Article 6 of the Indonesian journalism code of ethics that it is not allowed for Indonesian journalists both to abuse their professions and to accept bribes; (2) to provide explanations thatit is not permitted for professional journalists to receive gratuity, (3) to describe examples of violation cases of the Article 6 that the Indonesian journalists should not abuse their professionsas well as accept any bribes in the form of the online news writing discourses portal Kupastuntas.co. and Liputan6.com; and (4) to describe examples of cases related to the extra payment to journalists in the form of written discourses on the online news portal AyoBandung.com. This article uses a qualitative research method, in which data on cases of violations of the Article 6 on the online news portal Kupastuntas.co., Liputan6.com. and AyoBandung.com written descriptively.The data collected were secondary which were obtained by using observation techniques in the form of notes. Based on the presentation in this article, there are shown: (1) both the interpretation and the explanation of the Article 6; (2) the explanation of gratification; (3) examples of cases regarding Article 6; and (4) examples of cases of gratification. From the discussion and case examples presented, it was found that there was compatibility between the theory used and the case examples used.